Analisis Peran Balai Taman Nasional Manupeu Tanah Daru dan Laiwangi Wanggameti dalam Mengelola Pariwisata Berbasis Masyarakat: Studi pada Wisata Air Terjun Lapopu Kabupaten Sumba Barat - Antonius Nandito Laput; Marthina Raga Lay; Aspri Budi Oktavianto; Jeni Jacoba Therik (Student Research Journal, 2026)
This study examines the role of the Manupeu Tanah Daru and Laiwangi Wanggameti National Park Office (Balai TN MaTaLaWa) in managing community-based tourism at Lapopu Waterfall, Rewarara Village, Wanokaka District, West Sumba Regency. The research employed a qualitative descriptive approach to understand the implementation of community-based tourism management in the conservation area. Data were collected through observation, interviews, documentation, and literature study involving the National Park Office, village government, local communities, tourism managers, and tourists. The results indicate that Balai TN MaTaLaWa has performed its role as regulator, facilitator, catalyst, and dynamizer in tourism management. Its role as regulator is reflected in the establishment of tourism management rules and supervision of conservation areas. As a facilitator, the institution supports tourism facilities and community economic activities. As a catalyst, Balai TN MaTaLaWa builds cooperation among stakeholders, while as a dynamizer it provides training and tourism awareness education to local communities. The implementation of Community Based Tourism (CBT) has involved local communities in tourism activities, particularly as tour guides and environmental caretakers. However, tourism management still faces several challenges, including limited tourism human resources, inadequate supporting facilities, and unstable water discharge affecting the attractiveness of Lapopu Waterfall. Therefore, strengthening community capacity, improving infrastructure, and enhancing cooperation among stakeholders are necessary to support sustainable tourism management in the area.